Modeling of Sediment Transport - Pasquali, Davide (IntechOpen, 2022)
This book presents the latest developments and research in sediment transport. It includes five chapters that address sediment transport estimation, experimental investigation of the physical properties of porous media, and numerical approaches to sediment transport modelling.